P92Regulatory and functional analyses of Neuraminidase-1 in inflammatory processes after myocardial ischemia/reperfusion. (15th July 2014) - Gorst, I; Ricke-Hoch, M; Erschow, S; Scherr, M; Hilfiker-Kleiner, D
Abstract: Purpose: Implementation of PTA as standard treatment for patients with myocardial infarction (MI) reduced the mortality in the early phase. However, morbidity due to adverse cardiac remodelling has increased. In MI-patients, serum concentrations of free sialic acids are significantly elevated. Those are released from glycoconjugates by neuraminidases (Neu). Neu play important roles in various biological processes, i.e. inflammation, differentiation and metabolism. Here, we investigate the role and regulation of Neu1 in monocytes/macrophages (Mo/Mϕ) after cardiac ischemia/reperfusion (I/R).  Methods & results: Wild type mice undergoing cardiac I/R operation (50 min occlusion of the LAD followed by reperfusion) showed a significant up-regulation of Neu1 mRNA and protein expression in the ischemic area 3 d after I/R compared to sham operated mice (191±40%, p<0.001), whereas there was no difference between the two groups 14 d after I/R. Neu1 enzyme activity was also significantly increased on day 3 (403±90 mU/mg protein vs. 280±70 mU/mg protein, p<0.01). In the ischemic left ventricle, immunhistochemistry revealed a strong Neu1 expression in Mϕ and CD11b+ Mo/Mϕ isolated by MACS from infarcted murine hearts 3 d after I/R showed up-regulated Neu1 mRNA expression compared to CD11b+ Mo from the spleen (+79±55%). In vitro differentiation of the human monocytic cell line THP-1 into Mϕ by PMA increased the expression and activity of Neu1 (333±61 vs. mock, p<0.01). SiRNA-mediated down-regulation of Neu1 in THP-1 Mϕ resulted in a significant reduction of the expression of pro-inflammatory cytokines (IL-6: 47±11%, TNF-α: 68±7%, IL-1β: 78±8% vs. ctrl-siRNA, p<0.05), but had no effect on expression of the anti-inflammatory cytokine IL-10. The stimulation of THP-1 Mϕ with IL-6 had no effect on Neu1 expression. Furthermore, differentiation of primary human CD14+ Mo into pro-inflammatory M1 Mϕ by GM-CSF was associated with an up-regulation of Neu1 mRNA on day 4 (438±360%), whereas anti-inflammatory M2 (M-CSF) displayed no changes in Neu1 expression compared to CD14+ Mo. A possible regulatory mechanism of Neu1 expression in Mo/Mϕ could be the microRNA-125, as overexpression of miR-125a in primary human M1 resulted in down-regulation of Neu1 protein expression. Conclusion: Neu1 expression increases in the early phase after I/R and is mainly found in invading Mo/Mϕ, so that it seems to participate in the pro-inflammatory reactions via regulating cytokine expression. Therefore Neu1 may display a new therapeutic target after reperfusion of the infarcted heart to attenuate adverse effects of inflammation.